2014
DOI: 10.1016/s0185-2574(14)71396-6
|View full text |Cite
|
Sign up to set email alerts
|

Excavations in Nakum structure 99: new data on Protoclassic rituals and Precolumbian Maya beekeeping

Abstract: Structure 99, located on top of a large platform occupies a major and prominent part of the North Group complex of the Maya site of Nakum situated in the north-eastern area of Guatemala. Archaeological excavations realized in this structure during a few field seasons have revealed interesting data about the very last moment of Nakum's development during the Terminal Classic period (AD 800-900/950). It also revealed important traces of architectural and ritual activities from the still enigmatic Protoclassic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
0
11
0
2
Order By: Relevance
“…This dating was further confirmed by one radiocarbon date of AD 80–260 (2σ cal. ; Źrałka et al 2014: 107). All archaeological data indicate that Offering 9 and the ceramic tube date to the Terminal Preclassic or Protoclassic period.…”
Section: Archaeological Context and Dating Of The Artifactmentioning
confidence: 98%
See 4 more Smart Citations
“…This dating was further confirmed by one radiocarbon date of AD 80–260 (2σ cal. ; Źrałka et al 2014: 107). All archaeological data indicate that Offering 9 and the ceramic tube date to the Terminal Preclassic or Protoclassic period.…”
Section: Archaeological Context and Dating Of The Artifactmentioning
confidence: 98%
“…7 m high, which during its last architectural stage (in the Terminal Classic, circa AD 800–900/950) was surmounted by three superstructures (Figure 2b-c). The latter construction was extensively investigated during the recent research of the Nakum Archaeological Project when two tunnels, several trenches, test pits, and extensive clearing excavations were carried out (Źrałka et al 2008:77–92, 2014). They revealed that Structure 99 started as a low platform surmounted by a single chamber with a stairway on its southern face (the whole construction was denominated by us as Structure 99 Sub-1).…”
Section: Archaeological Context and Dating Of The Artifactmentioning
confidence: 99%
See 3 more Smart Citations